Turtle Nesting Habitat Conditions on Pandan Island, Pieh Island Conservation Area, West Sumatera - Prima, M.; Widhayanti, Arintika; Nugraha, Adiguna Rahmat (Universitas Muhammadiyah Surakarta, 2024)
Potential as a suitable habitat for turtles to settle and breed. The objective of this work is to assess the state of turtle nesting sites and evaluate the findings from turtle monitoring efforts in the Pieh Island Conservation Area. Observations were conducted directly from September 25th to September 30th, 2023. A quantitative method was employed. The materials that were utilized consist of green sea turtles (Chelonia mydas), hawksbill turtles (Eretmochelys imbricata), and olive ridley turtles (Lepidochelys olivaceae). The nesting habitat data encompasses information on the proximity of vegetation to the tidal limit, beach slope temperature and humidity levels, as well as the depth and quantity of eggs. Four stations serve as research sites. The distance of vegetation from the nests ranged from 7.6m to 13.4m, while the beach slope on Pandan Island varied between 3.62º and 6.19º. The temperature inside the nests ranged from 28ºC to 29.1ºC, with a humidity level of 77% to 88%. The nests had a depth of 50cm to 60cm. The results of this study show that Pandan Island Beach is a highly suitable site for turtle nesting.